Browsing the Origins of Comic Book Superheroes: Exploring WatchMojo.com as producers of video channel content - Andersen, Tem Frank (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2017)
This article tries to explore and explain the significance of comic book superheroes and their origin stories. The article presents an analysis of two selected case examples from the social video sharing site WatchMojo.com. The analysis focuses on four aspects or themes: Comic book hermeneutics, types of origin, subjectivization of superheroes, and user reactions. These analytical themes are based on an approach combining cultural semiotics, comic book superhero studies, studies in participatory culture, cultural studies and media user studies. The analysis provide some evidence to the claim, that superhero origin stories are of significance because its content is relevant to a dedicated number of internet users, and the video content both calls for and creates user reactions. Furthermore this interplay enacts the practice of categorizing and revitalizing as two important mechanisms vital for understanding this particular Internet video content.